Diaspora and Transnationalism Concepts, Theories and Methods - Bauböck, Rainer; Faist, Thomas (Amsterdam University Press, 2010)
Diaspora and transnationalism are widely used concepts in academic as well as political discourses. Although originally referring to quite different phenomena, they increasingly overlap today. Such inflation of meanings goes hand in hand with a danger of essentialising collective identities. This book therefore analyses diaspora and transnationalism as research perspectives rather than as characteristics of particular social groups. The contributions focus on conceptual uses, theoretical challenges and methodological innovations in the study of social ties that transcend nation and state boundaries. This volume brings together authors from a wide range of fields and approaches in the social sciences, as studying border-crossing affiliations also requires a crossing of disciplinary boundaries.